Usability Of “DFU Application” For Diabetic Foot Ulcer Prevention - Purnama, Bedy; Lindayani, Linlin; Mutiar, Astri; Erfianto, Bayu; Darmawati, Irma (Universitas Pendidikan Indonesia, 2025)
Introduction: The development of smart detection software may help reduce the number of decubitus ulcer infections by enabling early identification and management. Ensuring the usability and effectiveness of such technology is essential before widespread adoption. Objective: This study aimed to explore prospective users’ perceptions of the mobile app for detecting diabetic foot ulcer (DFU) infection, focusing on its usefulness, ease of use, and overall user satisfaction. Methods: The usability of the DFU app was assessed by experienced users. The evaluation included perceived usefulness, ease of use, and overall satisfaction. Standardized tools such as the System Usability Scale (SUS) and a specific app rating scale were used to collect user feedback. Results: The DFU app received usability ratings ranging from 0.50 to 0.88. The lowest rating was for performance quality (Mean = 0.50, SD = 0.12), while the highest was for integrity (Mean = 0.88, SD = 0.07). The overall usability score, as measured by SUS, was considered acceptable (Mean = 78.4, SD = 6.83). Most users reported no significant issues with using the app, except for difficulty understanding the language used in the interface, which was rated as a serious usability issue with a severity score of 3. Conclusions: Users perceived the DFU app as useful and efficient, particularly in detecting the risk of infection. Despite a noted language comprehension issue, the app demonstrated good overall usability and has the potential to support early intervention for decubitus ulcer prevention.